The Effect of Foreign Direct Investment, Labor, Manufacturing Industry and Government Expenditure on Economic Growth in Indonesia - Qanita, Qanita; Nasir, Muhammad (Grimsa Journal of Business and Economics Studies, 2025)
Progressive economic growth is a fundamental objective for all countries, including Indonesia, as it serves as a key indicator of national development and a means to enhance prosperity and public welfare. This study examines the impact of foreign direct investment, labor, the manufacturing industry, and government spending on economic growth in Indonesia. It utilizes secondary panel data from 34 provinces over the period 2018-2023 and applies a panel data regression method using the Common Effect Model (CEM). The estimation results show that both foreign direct investment and the manufacturing industry have a positive and significant effect on Indonesia’s economic growth, while labor and government spending exhibit an insignificant impact. Based on these findings, the study recommends the development of policies that attract foreign investment, particularly in the manufacturing sector, supported by adequate infrastructure development. Moreover, improving workforce quality through targeted education and training programs is essential. Government spending should be directed toward critical sectors and routinely evaluated to ensure that budget allocations effectively promote inclusive and sustainable growth.